Irreversible Land Water Availability Changes From a Potential ITCZ Shift During Temperature Overshoot - Norman Julius Steinert; Jörg Schwinger; Robin Chadwick; Jong‐Seong Kug; Hanna Lee (Earth's Future)
Abstract Without rapid emission reduction, it is increasingly likely that global temperatures will overshoot 1.5°C before carbon dioxide removal may help reverse warming. Such temperature overshoots affect the future hydrological cycle, with implications for land water availability. However, the hydrological response to such temperature overshoots is not well understood. Here, we investigate regional and seasonal changes of precipitation minus evaporation (P − E) in an ensemble of Earth system model simulations of temperature overshoot. Most climate models broadly show P − E reversibility after overshoot. However, models exhibiting an irreversible shift of the intertropical convergence zone (ITCZ) during the temperature overshoot experience reduced wet‐season and enhanced dry‐season land water availability in tropical regions, which has long‐lasting effects on the amplitude of P − E seasonality after the overshoot, constituting irreversible changes on human timescales. While some regions may experience alleviating seasonal hydrological conditions, others are subject to more intense seasonality. Half a century of CO2‐stabilization after the temperature overshoot only halves the legacy effects of the overshoot on land water availability on over 23% of the world population in 12% of the global land area, covering regions of various hydrological regimes. Based on the model ensemble presented here, a strong irreversible shift of the ITCZ after an overshoot is a low‐probability but high‐impact outcome that would entail long‐lasting hydrological changes with consequences for ecosystems and human societies.